2020
DOI: 10.1259/bjr.20200894
|View full text |Cite
|
Sign up to set email alerts
|

Reporting incidental coronary, aortic valve and cardiac calcification on non-gated thoracic computed tomography, a consensus statement from the BSCI/BSCCT and BSTI

Abstract: Incidental coronary and cardiac calcification are frequent findings on non-gated thoracic computed tomography (CT). We recommend that the heart is reviewed on all CT scans where it is visualised. Coronary artery calcification is a marker of coronary artery disease and it is associated with an adverse prognosis on dedicated cardiac imaging and on non-gated thoracic CT performed for non-cardiac indications, both with and without contrast. We recommend that CAC is reported on all non-gated thoracic CT using a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 58 publications
(68 reference statements)
0
28
0
Order By: Relevance
“…[31] Based on our hospital policy, together with recent advice of the ACR and BSCI/BSCCT and BSTI we classified CAC as a potentially significant IF. [22,27,32,33] This difference in definition of a potentially significant IF is hence merely caused by change in insight overtime between the present study and the somewhat older publications of lung cancer screening studies (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015).…”
Section: Discussion (1158)mentioning
confidence: 64%
See 2 more Smart Citations
“…[31] Based on our hospital policy, together with recent advice of the ACR and BSCI/BSCCT and BSTI we classified CAC as a potentially significant IF. [22,27,32,33] This difference in definition of a potentially significant IF is hence merely caused by change in insight overtime between the present study and the somewhat older publications of lung cancer screening studies (2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015).…”
Section: Discussion (1158)mentioning
confidence: 64%
“…CAC is a biomarker for atherosclerotic burden, and is associated with an increased risk of cardiovascular events, even in asymptomatic patients. [27] Knowing of the presence and extent of CAC may be valuable to patient and rereferring clinician, to increase patients awareness of atherosclerosis and discuss risk modulation interventions such as life style changes and introduction of cholesterol lowering medication (e.g. statin).…”
Section: Discussion (1158)mentioning
confidence: 99%
See 1 more Smart Citation
“…recommends that where the heart can be visualized on a CT-scan, it is reviewed. [27] However, in a study which used CT-scans from the NELSON trial, the impact of such incidental extra-pulmonary findings was demonstrated trivial compared to the specific purpose of lung cancer screening, notably without perceivable advantage for the small number of incidental detections. [28] AI has nevertheless proved to be valuable in coronary artery calcium (CAC) scoring of LDCT thorax scans.…”
Section: Discussionmentioning
confidence: 99%
“…In our survey comments included concerns around patient anxiety, unnecessary investigations and increased workload for radiology and cardiology departments. Other concerns that have been The recently published BSCI/BSCCT consensus statement on reporting incidental coronary, aortic valve and cardiac calcification on non-gated thoracic CT aims to address some of the concerns raised in this survey [33]. For coronary artery calcification it suggests a simple patient-based score for coronary artery calcification (none, mild, moderate, severe) and highlights that many patients with incidental calcification do not require further investigation [33].…”
Section: Discussionmentioning
confidence: 99%